Regionale Mobilität in der Sowjetunion - Vogelsang, Roland (ERDKUNDE, 1976)
Recent statistical publications permit the presentation of population movements in the Soviet Union at the level of smaller administrative units as well as in respect of the direction and intensity of individual migration streams. The typification of regional units according to net migration and mobility indicates fundamental regional differences. Apart from the Greater Moscow urban region migration gains are chiefly recorded by certain oblasts in the north, south and east. Migration losses chiefly occur in a strip which stretches from the south west to the south of Western Siberia. The traditionally more densely settled wedge thus grows larger and wider, at the same time diminishing in density. The peripherally situated oblasts with high migration gains are characterised by a high degree of fluctuation. The migration streams are summarized in stages with the aid of tables and maps. The net migration streams illustrate in detail the uneven structure of relations between the economic districts and between the macro-regions of the Soviet Union.